2017
DOI: 10.1038/oncsis.2017.81
|View full text |Cite
|
Sign up to set email alerts
|

Xanthine dehydrogenase downregulation promotes TGFβ signaling and cancer stem cell-related gene expression in hepatocellular carcinoma

Abstract: Xanthine dehydrogenase (XDH), a rate-limiting enzyme involved in purine metabolism, has an essential role in inflammatory cascades. Researchers have known for decades that XDH activity is decreased in some cancers, including hepatocellular carcinoma (HCC). However, the role of XDH in cancer pathogenesis has not been fully explored. In this study, we showed that low XDH mRNA levels were correlated with higher tumor stages and poorer prognoses in patients with HCC. Knocking down or inhibiting XDH promoted migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 55 publications
(80 reference statements)
0
32
0
Order By: Relevance
“…These findings suggest that certain geographic regions of tumor were more closely related to certain metastatic sites, while other metastatic sites were yet more divergent from the primary tumor. Distinct validated mutations in this cluster would be considered subclonal and included SF3B1, XDH, LTF, and TMEM2, all of which have been implicated in metastasis and poorer prognosis (19)(20)(21)(22). We also analyzed multiregion sequencing data from 2 cases of breast ACC undergoing transformation to high-grade triple-negative breast cancer previously reported by Fusco et al (23).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that certain geographic regions of tumor were more closely related to certain metastatic sites, while other metastatic sites were yet more divergent from the primary tumor. Distinct validated mutations in this cluster would be considered subclonal and included SF3B1, XDH, LTF, and TMEM2, all of which have been implicated in metastasis and poorer prognosis (19)(20)(21)(22). We also analyzed multiregion sequencing data from 2 cases of breast ACC undergoing transformation to high-grade triple-negative breast cancer previously reported by Fusco et al (23).…”
Section: Resultsmentioning
confidence: 99%
“…Deep sequencing and NMF clustering analysis depicted 1 cluster comprising exclusively metastatic lesions with distinct mutations (SF3B1, XDH, LTF, TMEM2) that may promote metastasis ( Figure 7). SF3B1 mutations are well established in cancer, contributing to alternative splicing and implicated in late metastasis in uveal melanoma (19), while XDH mutations have been shown to promote migration and invasion in hepatocellular carcinoma (20). LTF mutations affect cell motility, while TMEM2 (also known as CEMIP2) mutations appear to confer proinvasive and promigratory potential: both genes are known to be associated with breast cancer metastasis (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that in liver, kidney and breast cancer tissues, the expression level of XDH is signi cantly lower than normal tissues, purine catabolism is severely impaired, and anabolic enzymes are increased [16][17][18][19]. This change gives tumor tissue a selective growth advantage through the rescue pathway of nucleic acid biosynthesis [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…During egg development of B. mori the amount of uric acid gradually declines until blastokinesis, after which it increases until egg pigmentation [26]. Remarkably, XHD knockdown has been shown to enhance cell mobility and invasion of HepG2 cells, although no effect on cell proliferation was observed [27]. Furthermore, XDH converts retinoic acid to 9-cis retinal [28], and activity of the enzyme is essential in order for JH to induce bristle formation and cuticle production on the abdominal epidermis during pupal and adult development [29].…”
Section: Discussionmentioning
confidence: 99%